La liberté comme principe. L’éducation des enfants chez les Galibi-Marworno du Brésil et la scolarisation - Antonella Tassinari (Cahiers de la Recherche sur l'Education et les Savoirs)
Galibi-Marworno’s education is based on a principle that children should live freely to develop a strong and healthy body, to acquire useful knowledge in everyday life, to "take the community’s rhythm." The paper presents and analyzes some characteristics of children’s education, especially the way they learn to master the knowledge related to daily activities. The ethnographic observation reveals the importance of non-verbal aspects of learning, highlighting the initiative of the children who have to be resourceful and creative in a process largely based on imitation in which they participate actively.From the standpoint of public policy, these learning processes are often considered contradictory to school rhythms and even dangerous for the well-being of children. Yet from the perspective of families, who had school education since 1934, there is no contradiction, they are both considered important and complementary processes for the development of children. This article propose some clues in order to reflect about contemporary school education challenges of children Galibi-Marworno.